A sustainable approach for lignin valorization by heterogeneous photocatalysis. Issue 3 (16th November 2015) - Li, Shao-Hai; Liu, Siqi; Colmenares, Juan Carlos; Xu, Yi-Jun
Abstract : Photocatalysis as an approach for lignin valorization from energy and environmental viewpoints. Abstract : The depletion of the Earth's fossil fuel reserves and the rapid increase in the emission of greenhouse gases and other environmental pollutants are driving the development of renewable energy technologies. Lignin is one of the three main subcomponents of lignocellulosic biomass in terrestrial ecosystems and makes up nearly 30% of the organic carbon sequestered in the biosphere. As a result of its rich content of aromatic carbon, lignin has the potential to be decomposed to yield valuable chemicals and alternatives to fossil fuels. However, the complex and stable chemical bonds of lignin make the depolymerization of lignin a difficult challenge with regard to its valorization. In this review, we highlight recent advances in the selective decomposition of lignin-based compounds via photocatalysis into other value-added chemicals and the treatment of waste water containing lignin. The photocatalytic transformation of lignin under mild conditions is particularly promising.